2022
DOI: 10.1021/acsbiomaterials.1c00834
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Polarization by Mineralized Collagen Coating to Accelerate the Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: Osteogenesis on the interface between the implant and host bone is a synergistic processing of multiple systems involved in immune response, angiogenesis, osteogenesis, etc. However, regulation of the osteoimmune microenvironment on the implant surface to accelerate the osteogenesis through manipulating the polarization of macrophage phenotype is still beginning to be explored. We here demonstrate that macrophage phenotype is able to be regulated by decoration of mineralized collagen (MC) coating on the titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…In this study, our prepared EGCG-based hydrogel alleviated ROS accumulation in osteoporotic microenvironment, thus reducing the number of pro-inflammatory M1 macrophages and increasing the number of M2 regenerative macrophages. It is worth mentioning that the effect of Ti-BMSCs@HG group on inducing macrophages to polarize from M1 to M2 is more obvious than that of Ti-HG group, which may be attributed to the immune regulation of loaded rBMSCs in a relieved osteoporosis microenvironment (Liu C. et al, 2022;Shao et al, 2022).…”
Section: D-printed Bioactive Prosthesis Interface Reshapes Osteogenic...mentioning
confidence: 99%
“…In this study, our prepared EGCG-based hydrogel alleviated ROS accumulation in osteoporotic microenvironment, thus reducing the number of pro-inflammatory M1 macrophages and increasing the number of M2 regenerative macrophages. It is worth mentioning that the effect of Ti-BMSCs@HG group on inducing macrophages to polarize from M1 to M2 is more obvious than that of Ti-HG group, which may be attributed to the immune regulation of loaded rBMSCs in a relieved osteoporosis microenvironment (Liu C. et al, 2022;Shao et al, 2022).…”
Section: D-printed Bioactive Prosthesis Interface Reshapes Osteogenic...mentioning
confidence: 99%
“…[64,65] The changes in bone turnover rates and activated signaling pathways may influence the hyaline construct mimicry of a biomaterial and may affect long-term tissue integration, since mineralized collagens can induce osteoformation. [66] The synovial cavity is protected by a barrier of fibroblastlike synoviocytes (FLS) and locally resident synovial macrophages. [67,68] FLS are the main cells producing HA and joint lubricants such as proteoglycan 4 (lubricin), as well as matrix components for the synovial ECM such as fibronectin and collagens.…”
Section: Articular Pathologies Engage the Whole Joint Organmentioning
confidence: 99%
“…[ 64,65 ] The changes in bone turnover rates and activated signaling pathways may influence the hyaline construct mimicry of a biomaterial and may affect long‐term tissue integration, since mineralized collagens can induce osteoformation. [ 66 ]…”
Section: The Pathological Environment Can Influence Biomaterials Inte...mentioning
confidence: 99%
“…Traditional bone tissue engineering approaches, such as incorporating anti-inflammatory cytokines and constructing bioactive coatings, focus on altering the biochemical property of biomaterials to modulate macrophage polarization toward M2 phenotype. Nevertheless, limited half-lives, introduction of exogenous microorganisms, and lack of active response property restrict their use in clinical practice. , Actually, macrophages are highly sensitive not only to biochemical cues but also to mechanical and topographical cues from the microenvironment. Once perceived by macrophages through the receptors on the cell membrane, mechanical stimulations can be transmitted to the nucleus along the cytoskeleton and converted into biosignals to activate gene transcription and drive specific phenotypic transformation. Recently, a study has observed that stretch-activated macrophages polarize into M2 phenotype and remarkably upregulate the expression of bone morphogenetic protein-2 (BMP-2), thereby inducing osteogenesis of mesenchymal stem cells (MSCs) . However, exerting mechanical stimulation on macrophages in vivo with a spatiotemporal controllable way still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%